2015
DOI: 10.1200/jco.2014.59.9324
|View full text |Cite
|
Sign up to set email alerts
|

Pemetrexed Plus Cisplatin Versus Gemcitabine Plus Cisplatin According to Thymidylate Synthase Expression in Nonsquamous Non–Small-Cell Lung Cancer: A Biomarker-Stratified Randomized Phase II Trial

Abstract: With regard to response rate and progression-free survival, pemetrexed/cisplatin was superior to gemcitabine/cisplatin in the TS-negative group but not in the TS-positive group, indicative of TS expression as a potential predictive marker. Additional prospective studies involving larger cohorts are warranted to confirm the predictive role of TS expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 20 publications
(27 reference statements)
3
62
0
Order By: Relevance
“…Some studies such as the published by Chang et al did not show statistically significant results supporting the use of TS as a potential biomarker [29]. A very recent prospective study stratified the patients according to TS expression by IHC showed better response rate and progressionfree survival for pemetrexed/cisplatin in the group lacking TS expression [30]. Nevertheless, this is not yet a standard recommendation for clinical practice.…”
Section: Pemetrexedmentioning
confidence: 93%
“…Some studies such as the published by Chang et al did not show statistically significant results supporting the use of TS as a potential biomarker [29]. A very recent prospective study stratified the patients according to TS expression by IHC showed better response rate and progressionfree survival for pemetrexed/cisplatin in the group lacking TS expression [30]. Nevertheless, this is not yet a standard recommendation for clinical practice.…”
Section: Pemetrexedmentioning
confidence: 93%
“…More recently, Sun and collaborators [39] reported data from an observational phase II study where they prospectively investigated the correlation between tumor baseline expression of TS and outcome in patients with nonsquamous NSCLC randomly assigned to either pemetrexed/cisplatin or gemcitabine/cisplatin treatment. Low-TS protein levels were predictive of significantly higher response rates and longer progressionfree survival (PFS) in patients treated with pemetrexed/cisplatin compared to the gemcitabine/cisplatin group.…”
Section: Pharmacogenetics Of Pemetrexedmentioning
confidence: 99%
“…However, the efficacy of this preferred chemotherapeutic regimen is very limited, with response rates of 30% to 40%, and progressionfree survival (PFS) of about 4-6 months (3)(4)(5). Despite a large number of promising studies demonstrating the expression level of enzymes targeted by pemetrexed (6,7) and enzymes involved in nucleotide excision repair (NER) of DNA-platinum adducts (8) can be used to predict response to pemetrexed plus cisplatin treatment, the translation of these scientific data from bench to the bedside has not yet occurred. The detection assays, tissue types and antibodies used in previous studies, which lead to inconsistent results, needed to be standardized in all current clinical trials (9).…”
Section: Introductionmentioning
confidence: 99%